Effect of Different Pre-Freezing Time on Quality of Frozen Fat-Tailed Ram Semen - Sigit Bintara; Andriyani Astuti; Panjono Panjono; Tri Anggraeni Kusumastuti (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
This study aimed to determining the effect of temperature changes on the sperm quality of fat-tailed sheep during the freezing process using a microcontroller. This study was conducted from April to October 2018 at the Laboratory of Animal Physiology and Reproduction, Faculty of Animal Science UGM. The study was used twelve mature ram. The methods were conducted by collecting semen using artificial vagina, semen dilution, freezing semen, thawing and semen quality test. The pre-freezing temperature time were grouped for 6, 9, and 12 minutes. Data of frozen semen quality (motility, viability, and abnormality) the data were analyzed using one-way ANOVA and the study was arranged using Completely Randomized Design (CRD). The average of spermatozoa motility after semen freezing with a 5 to -140°C decrease in pre freezing temperature for 12 minutes (50±5.3%) was significantly different (P<0.05) compared to 9 minutes (48±4.8%) and 6 minutes (43±4.8%). The average of spermatozoa viability after semen freezing with a decrease in pre freezing temperature of 5 to -140°C for 12 minutes (55±4.7%) was significantly different (P<0.05) compared to that for 9 minutes (52±3.5%) and 6 minutes (49±5.7%). The average of spermatozoa abnormality after freezing with a decrease in pre freezing temperature of 5 to -140°C for 6, 9, and 12 minutes was not significantly different (10±2.4%, 9±0.8%, and 10±0.9%, respectively). Based on the findings, it is possible to conclude that semen freezing at a lower pre-freezing temperature of 0 to -140°C for 12 minutes can improve the quality of freezing results.